VD_FINDINFO HC / 2015 / 684 vom 8. Juli 2015 - VD Tribunal cantonal (2015)
HYPOTHÈQUE LÉGALE, COMMUNAUTÉ DES COPROPRIÉTAIRES D'ÉTAGES, GÉRANTSENS GÉNÉRAL | 712i al. 1 CC, 712i al. 2 CC, 712t al. 1 CC, 712t al. 2 CC